Analisis Implementasi Electronik Government Melalui Program Kareba (Karcis Elektronik Kawasan Bira) Dinas Pariwisata di Kabupaten Bulukumba - Mutdmainnah Ma (Departemen Ilmu Pemerintahan Fisip Unhas, 2024)
This study aims to determine the form of electronic government implementation through the BIra area electronic ticket program (KAREBA) of the Tourism Office in Bulukumba Regency. The type of research used is qualitative research. The location of this research is the Tourism Office of Bulukumba Regency. While the types of data used are primary data and secondary data. Data collection techniques used are observation, interviews, literature studies, and documentation. The data analysis technique used is qualitative analysis. The results of the study indicate that the implementation of Electronic Government through the Bira Area Electronic Ticket Program (KAREBA) of the Tourism Office of Bulukumba Regency uses the theoretical approach of Indrajat (2006) which consists of Government to Citizen (G2C), Government to Business (G2B), Government to Government (G2G), and Government to Employees (G2E) which have run quite well but still need to be improved.